Posição do incisivo inferior e dimensão alveolar vestibular no tratamento da má-oclusão de classe II - Araujo, Laura Lütz de (2013)
The aim of this study was to evaluate lower incisors position, buccal alveolar bone dimensions of the mandibular symphysis and clinical crown height of lower incisors of Class II division I malocclusion individuals before and after orthodontic treatment during growth. The sample consisted of pre and post treatment lateral teleradiographs and dental casts from 35 individuals with Class II malocclusion and ages between 9 and 12 years on the first evaluation, treated with headgear and orthodontic fixed appliance. The control group consisted of 46 subjects with Class II malocclusion and the same age of treated group individuals. Measures of lower incisor position and symphysis dimensions were taken on lateral teleradiographs and incisor clinical crown height was measured on dental casts. For comparison between T1 and T2 measures, paired Student t test was applied and for comparison between the groups, independent Student t test was used. Mann-Whitney non parametric test was applied to compare mean differences between the groups. To analyze the correlation between the measures, the Pearson correlation coefficient was used. Results were considered significant at a significance level of 5% maximum (p<0.05). Results indicated an increase in lower incisor inclination of 3.7° in relation to the mandibular plane and 3.9° in relation to NB line (p=0.000), increase on the distance of the cementoenamel junction to the buccal alveolar crest of 0.44 mm (p=0.000), decrease on buccal alveolar bone thickness at half of the root of 0.24 mm (p=0.005) non significant if compared to control group and increase of 1.6 mm on thickness of the buccal alveolar bone at the apex (p=0.000). Clinical crown height presented a non-significant increase of 0.14 mm. No significant correlation was found between the amount of lower incisor proclination and the amount of alterations of the symphysis or of the clinical crown height. The treatment of Class II malocclusion during growth period with headgear and fixed appliance resulted in slight vestibularization of lower incisors, increase on the distance of the cementoenamel junction to the buccal alveolar crest and increase on the distance of the apex to the buccal contour of the symphysis.